2007
DOI: 10.1143/jjap.46.3333
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Angle Antireflection Effect of Subwavelength Structures for Solar Cells

Abstract: The angle-dependent reflectivity of several surface structures was analyzed and evaluated with the viewpoint of solar cell applications. Numerical analysis showed that a Si subwavelength structure (SWS) maintains a lower reflectivity at large incident angles than conventional light-trapping techniques such as a random pyramid texture, and that it can contribute to increasing the output power of solar cells under oblique irradiation. This wide-angle antireflection effect was demonstrated by fabricating test cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 11 publications
2
42
0
Order By: Relevance
“…In order to meet the broadband antireflective requirements for III-V multi-junction solar cells, new ARCs with broadband antireflective properties have been studied. Subwavelength structures (SWSs) with a tapered profile and a period smaller than the wavelength of the incident light have been proven to suppress the surface reflection over a wide spectral range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] as well as wide incident angles [11,14]. The wavelength range with good antireflective properties is determined by adjusting the geometrical factor of the SWS [6] and the optical characteristics of the material on which the SWS is fabricated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to meet the broadband antireflective requirements for III-V multi-junction solar cells, new ARCs with broadband antireflective properties have been studied. Subwavelength structures (SWSs) with a tapered profile and a period smaller than the wavelength of the incident light have been proven to suppress the surface reflection over a wide spectral range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] as well as wide incident angles [11,14]. The wavelength range with good antireflective properties is determined by adjusting the geometrical factor of the SWS [6] and the optical characteristics of the material on which the SWS is fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…The additional complex and repetitive processes required for the fabrication of the SWS result in a longer fabrication time and thus a higher cost. Additionally, the optical and electrical characteristics of the solar cells may be degraded due to thermal, physical, or chemical damage which arises during the direct fabrication of the SWS on top of the solar cells [13,14]. The indirect integration of SWSs on solar cells can also improve the performance of solar cells without compromising the optical and electrical characteristics of the devices by avoiding the thermal, physical, or chemical damage associated with direct integration methods, as SWS fabrication processes are completely separated from the fabrication steps of the solar cell.…”
Section: Introductionmentioning
confidence: 99%
“…17 When used on the front surfaces, they can also decrease reflection. 18 Third, the grating period should be slightly smaller than the typical wavelength. If the period is too small, light does not sense the structural details and optical diffraction is weak.…”
Section: General Design Considerationsmentioning
confidence: 99%
“…Several studies of sub-micrometer gratings (SMG) on c-Si surface have shown ultra-low reflectivity at normal incidence and low reflectivity at large angles of incidence (AOI) was also demonstrated with a single wavelength [2][3][4][5]. The previous researches have shown that sharp nanostructures such as nano-cones or pyramids, exhibit broadband antireflective properties at normal incidence and large AOI [6][7][8][9]. However, sharp nano-tips may not be preferred in photovoltaics as they substantially result in considerable surface states that trap photo-generated carriers and also increase challenges in making ohmic contacts for electrodes.…”
Section: Introductionmentioning
confidence: 99%